Knowledge, Attitude and Perception of Private Dental Practitioners Towards Medical Emergencies in Klang Valley, Malaysia - Nor Azura Ahmad Tarmidzi; Nalisha Mohamed Ramli; Norashikin Amran; Husna Najihah Norazmi; Nur Saniah Mohd Arifin (Ectodermal Dysplasia Group Turkey, 2024)
Journal of International Dental and Medical Research; Diyarbakir Vol. 15, Iss. 2, (2022): 649-655.